Radiation-induced long-term alterations in hippocampus under experimental conditions - Bálentová, S; Hajtmanová, E; Kinclová, I; Lehotský, J; Dobrota, D; Adamkov, M (Klinicka onkologie, 2012)
BACKGROUNDS: The aim of the present study was to investigate the effect of ionizing radiation on the cell population that co-forms hippocampal formation in an adult rat brain. MATERIALS AND METHODS: Adult male Wistar rats were exposed to whole-body irradiation with fractionated doses of gamma rays (the total dose of 4 Gy). Thirty, 60 and 90 days after irradiation the cell-specific types housed in the CA1, CA3 subregions and adjacent layers were labelled using immunohistochemistry for specific cell phenotypes; Ki-67 marker was used for proliferating cells and GFAP for detection of astrocytes. RESULTS: During the 30th day post-exposure, a considerable increase in the numbers of Ki-67-positive cells was seen. Moreover, significant decline in the density of neurons, mostly in the CA1 subregion, was observed on the 60th day. Slight overaccumulation of Ki-67-positive cells was seen in CA1 area 90 days after radiation treatment. Temporary decrease of GFAP-positive astrocytes was seen thirty days after irradiation, followed by their subsequent increase 60 days after exposure. Secondary decrease of GFAP-positive cells in both of regions was found in the group surviving 90 days post-irradiation. CONCLUSION: Results showed that radiation response of neurons and astrocytes that form the adult hippocampus may play contributory role in the development of prognostically unfavourable adverse radiation-induced late effect.
Keywords: Glial Fibrillary Acidic Protein; Gamma Rays; gliový fibrilární kyselý protein; krysa rodu Rattus; Hippocampus; záření gama; zvířata; Immunohistochemistry; hipokampus; Ki-67 Antigen; imunohistochemie; potkani Wistar; antigen Ki-67; Rats, Wistar; Male; Astrocytes; dávka záření; Rats; Radiation Dosage; Animals; astrocyty; mužské pohlaví